Financing the sustainable management of Rwanda's protected areas - Onil Banerjee; Martin Cicowiez; Thomas Ochuodho; Michel Masozera; Bernabas Wolde; Pankaj Lal; Sebastian Dudek; Janaki R.R. Alavalapati (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2017)
Rwanda's Nyungwe National Park is a biodiversity hotspot with the most endemic species in the ecoregion as well as the highest number of threatened species internationally. In addition to great biological diversity, Nyungwe National Park supplies significant ecosystem services to the Rwandan population including water provisioning and tourism services. Tourism in the Park has strong potential for improving the sustainable management of the Park for continued provision of natural habitat and critical ecosystem services. This paper explores quantitatively the economic impacts of adjustment in Park visitation fees and tourism demand as a source of revenues to improve Park tourism opportunities and ongoing operations and maintenance where budgetary restrictions are particularly acute. The methods developed in this paper are novel in integrating the results of stated preference techniques with regional economy-wide modelling approaches to capture multi-sectoral, direct, indirect and induced impacts. Such methods have strong potential for assessing revenue generation alternatives in other contexts where Park Managers are faced with the need to generate additional revenue for sustainable park management while facing diminishing budget allocations.
Keywords: 330; Financing protected areas; economy-wide regional model; park fees; tourism demand; stated preference; Rwanda